PROCESS OPTIMIZATION FOR PRODUCTION OF ALKYL POLYGLYCOSIDES NONIONIC SURFACTANT USING RESPONSE SURFACE METHODOLOGY - Adisalamun, Djumali Mangunwidjaja, ani suryani, Titi candra Sunarti dan Yandra Arkeman (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
ABSTRACTDevelopment of the surfactant is strongly influenced by using material to produce alkyl polyglycosides (APG) surfactant, such as starch or glucose and dodecanol. The objectives of this study were to obtain optimization of process conditions for the APG production from glucose and dodecanol using the response surface methodology and to characterize the APG. The independent variables used were glucose-dodecanol mol ratio of 1:3 to 1:6 and acetalization temperature of 100-120oC. The optimum process conditions for the synthesis of APG from glucose was obtained at mole ratio of glucose to dodecanol of 1:4.7 and temperature of 111.4°C with the APG emulsion stability of y 75%. The optimum process conditions were verified to strengthen the model equations obtained using response surface method. The results of verification were tested surface tension, interfacial tension, HLB, and confirmation of its structure. Surface tension and interfacial tension decreased indicated by the increasing concentration of surfactant. HLB obtained was the O/W emulsifier and as a solubilizing agent.Keywords: alkyl polyglycosides(APG), dodecanol, emulsion stability